ANALYSIS OF DIVIDEND POLICY AND INTEREST RATE POLICY OF COMMERCIAL BANKS ON BONDS (American Journal of Business Management, Economics and Banking, 2024)
The article examines the meaning and significance of the concept of "Analysis of the dividend policy of commercial banks and interest rate policy on bonds", the level of profitability and liquidity when attracting financial resources from the capital market through securities, the level of profitability. on preferred shares, the profitability of corporate bonds, the practice of paying dividends in the case of Ipotekabank OTP is implemented.